Pemahaman Hadis Ali Mustafa Yaqub dan Kontribusinya Terhadap Pemikiran Hadis di Indonesia - Muhammad Qomarullah (AL QUDS : Jurnal Studi Alquran dan Hadis, 2020)
Ali Mustafa Yaqub’s Understanding of Hadiths and his Contributions to the Thoughts of Hadiths in IndonesiaThis is a qualitative study that delves into the hadith figure of the 20th century, Ali Mustafa Yaqub. This study aims to reveal Ali Mustafa Yaqub's understanding of hadiths according to his thoughts alongside his contributions to the thoughts of hadiths in the contemporary era. According to him, the study of hadiths in the current era must include Mustalah al-Hadith, Takhrij al-Hadith, Fiqh al-Hadith, and Difa 'an al-Hadith. According to him, the authenticity of hadiths can be known by comparing them with other hadiths from peers, in terms of time, from various narrators, and also from teachers or the works in hadith books. In so doing, the credibility of hadiths is known. Subsequently, his contributions to the thoughts of hadiths extend to introducing orientalist thinking and defending scholars, developing the method of understanding hadiths by establishing Darussunnah Islamic Boarding School, and writing various hadith thoughts that contain reconstructions of the understanding of hadiths in the form of either criticism or new thoughts about hadiths such as the meaning of bid'ah or hadiths in community debates related to law